ИСТОЧНИКИ ЗАГРЯЗНЕНИЯ ВОДОЕМОВ БАССЕЙНА ВЕРХНЕГО ДОНА - Маликов В.С. (My University, 2003)
The quartz glass-production sands are spread in the Aptian and probably in the Albian deposits of the Voronezh area. The Bogdanovka deposit of the glass-production sands is discovered.
Keywords: Albian; Aptian; 556.678.543.31; Mesozoic::Cretaceous::Lower::Albian; Mesozoic::Cretaceous::Lower::Aptian; Мезозой::Меловая::Нижний::Альбский; Мезозой::Меловая::Нижний::Аптский